Anaerobically digested dairy fiber in soilless potting media for poinsettias - John R. Lamont; George C. Elliott (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Sphagnum peat moss has been a primary component of soilless potting media for decades. Concerns over the sustainability of harvesting peat have fostered a search for renewable media components. Anaerobically digested dairy fiber (ADDF), a by-product of methane production, shows promise as an alternative to peat. Methods Poinsettias (Euphorbia pulcherrima âClassic Redâ) were grown in media containing peat-perlite in a 4:1 ratio or peat-ADDF-perlite in a 2:2:1 ratio. Bulk density, container capacity, water-holding capacity, pH and EC of both mixes were evaluated before planting. Shoot height, shoot fresh weight, shoot dry weight and leaf tissue nutrient concentrations of plants were measured at commercial maturity. PourThru samples were taken from pots regularly to evaluate phosphate leaching potential from ADDF. Results There were no differences in physiochemical properties between mixes. Poinsettias grown in the peatADDF-perlite were significantly taller and had greater shoot fresh weight, shoot dry weight and leaf tissue N, P, Mn, Na and Zn concentrations than control plants. PourThru samples from pots containing peat-ADDF-perlite had greater phosphate concentrations than peat-perlite for approximately 5 weeks. Conclusions The ADDF used in this trial can be used as a 50 % substitute for peat in potting media for poinsettias and contains significant amounts of plant available nutrients. Additional nutrients supplied by ADDF should be carefully managed as they can contribute to plant growth or leaching pollution. Using ADDF in media could provide growers with a local, renewable substitute for peat and provide supplemental income to dairy farmer.